Bibliometric Analysis of the Utilisation of FINDRISC in Patients with Diabetes: 2005-2021 - M. Rifqi Rokhman; Bustanul Arifin; Zulkarnain Zulkarnain; Saidah Rauf; Dyah Aryani Perwitasari (Borneo Journal of Pharmacy, 2022)
Research on risk factors for diabetes (DM) is growing. Identification of these risk factors aims to prevent DM as early as possible. This study intends to identify the utilization of the Finnish diabetes risk score (FINDRISC) and its development using bibliometric analysis. The keywords “FINDRISC AND Diabetes” were used to search for articles published in 2005-2021 in PubMed. A total of 249 articles were analyzed based on the number of publications per year, journals that publish the papers, number of publications by author and year of publication, number of publications by affiliation and year of publication, number of publications by country of origin of authors and year of publication, number of keywords, number of citations, types of articles, specific topics, and theme mapping. The data visualization was obtained from the Scopus database and the VOSviewer and Biblioshiny applications. Despite the increase in publications, the number of publications on FINDRISC in DM patients is still very few per year, with 92.8% being the primary study. Based on clusters of the country of origin, publications are still dominated by researchers from countries in the European region, and the researchers intensely relate to each other through citations. Research themes related to FINDRISC are not limited to DM risk factors. This study is the first study of a bibliometric analysis of the utilization of FINRISC in DM patients. The analysis results can be used to evaluate existing research gaps and identify future research opportunities.